Hybrid methods of working with databases in JEE applications - Jóźwicka, Katarzyna; Mitrus, Mariusz (Journal of Computer Sciences Institute, 2019)
The article presents the research on hybridization of methods of working with databases in JEE applications. The test applications were made based on the JDBC interface, Hibernate and Spring framework. Application performance analysis covered the execution time and RAM usage for basic CRUD operations in the database.